Transformational Leadership Based on Islamic Values for Organizational Change: A Strategic Approach at the Madiun Forestry Service - Yulia Anggraini; Dwijo Saputro (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
The success of public sector organizations in adapting to environmental, technological, and policy shifts depends on leadership effectiveness and adaptive managerial strategies. This study explores the role of transformational leadership in managing organizational change at the Madiun Region Forestry Service Branch through the lenses of Resource-Based View (RBV) and Dynamic Capabilities. The study identifies key strategic resources and analyzes the organization’s capacities in sensing, seizing, and transforming. Findings reveal that transformational leaders foster a collaborative and adaptive work culture, accelerate digital transformation, and enhance synergy between government and forestry communities. The integration of Islamic leadership values amanah (trust and responsibility), shura (deliberation), and ihsan (excellence) adds ethical depth and strengthens value-based leadership practices. This research contributes by providing a conceptual model linking transformational leadership, RBV, and dynamic capabilities to promote sustainable, ethical, and innovationoriented transformation in public sector organizations.